Short Rotation Forestry Expansion Drives Carbon Sequestration in Biomass but Not in Soil - Getachew Gemtesa Tiruneh; Asmamaw Alemu; Jennie Barron; Fantaw Yimer; Erik Karltun (GCB Bioenergy)
ABSTRACT A significant land use change from cropland to short rotation forestry (SRF) has taken place in the northwestern (NW) Ethiopian highlands where a fast‐growing tree species, Acacia mearnsii, is cultivated to produce charcoal for urban markets. We investigated the extent of this land use change, its impact on the landscape carbon (C) budget, and its implications for climate change mitigation by combining field studies with remote sensing. We analyzed land use and land cover changes between 2005 and 2022 using Google Earth Pro imagery and validated the result with ground truthing through field observations. We estimated C stocks using soil and biomass samples collected from A. mearnsii plantation fields managed by smallholder farmers across three rotations and stand ages, as well as from cropland and other major land use types. Between 2005 and 2022, 60% of the cropland in the studied district was converted to A. mearnsii plantations. Our analysis showed that A. mearnsii cultivation had the highest spatial cover in 2017. However, a disease outbreak in 2020 resulted in a 40% reduction in cultivated area by 2022 compared to 2017 levels. The expansion of A. mearnsii cultivation increased total landscape C stocks by 21%, equivalent to a net sequestration of 0.3 Mt CO2 year−1 in the study district. This corresponded to 2.3% of Ethiopia's total annual fossil fuel emissions in 2021. The observed gain was due to C accumulation in standing biomass. In contrast, soil C stock showed a declining trend with successive rotations, though this change was not statistically significant. The main contribution of A. mearnsii based SRF in NW Ethiopia to the C budget is its potential to reduce dependence on natural forest for charcoal and firewood production.